Imperial Patchwork “Flickenteppiche” as a Historical Metaphor for Chaos, Federalism and Diversity - Wüst, Wolfgang (Advances in Social Sciences Research Journal, 2022)
With the recent research on the importance of the Estates, whose function often went far beyond questions of taxation, the Imperial Circles and the simultaneous deconstruction of European state formation as an absolutist top-down process the view of the “co-organizing intermediate levels” changed. This is how Johannes Burkhardt described these regional images in 2006 in “Gebhardt. Handbuch der Deutschen Geschichte.” The new view of the Old Empire has been well received by research in regional history, especially since differentiations on small-scale rule and organization in Bavaria, Baden-Württemberg, Hesse, Thuringia, Saxony and other federal states have traditionally been and still are part of the core business of this discipline. “Flickenteppiche” as colourfully woven objects of diversity are certainly still products in demand in the textile industry and consumer society, but they are just as unsuitable as an explanatory model for the coherence of the Empire and its Imperial Circles as they are for analyzing power and rule in the early modern period. In their figurative meaning of the word, patchwork carpets ignore communicative processes for decision-making just as much as they register cross-border action and design as a quantité négligeable.